ЗНАЧЕНИЕ ЛИТЕРАТУРЫ ДЛЯ ОБЩЕСТВА. ПРОБЛЕМЫ СОВРЕМЕННОЙ ЛИТЕРАТУРЫ - Мубараков, М.Б. (SCIENCE and SOCIETY, 2025)
The article discusses the modern problems of Russian literature. The main examples are also given with a detailed explanation of the material presented. This scientific work also considers the options for the revival of modern Russian literature.